The dark triad and subjective well-being: the mediating role of cognitive-emotional regulation strategies. - Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Megías-Robles, Alberto; Fernández-Berrocal, Pablo (Wiley, 2022)
The dark triad (DT) is composed of psychopathy, narcissism, and Machiavellianism. These traits have usually been correlated with maladaptive strategies of emotion regulation. In turn, these types of strategies have shown a negative relationship with the components of subjective well-being (SWB): affective well-being (AWB) and cognitive well-being (CWB). The principal objective of the present study was to analyze the possible mediating role of adaptive and maladaptive cognitive-emotional regulation strategies in the relationship between the DT and SWB components. For this purpose, a community sample of 678 participants (Mage = 35.03; 53.1% women) completed the Satisfaction with Life Scale (SWB), the Positive and Negative Affect Schedule (PANAS), the Cognitive Emotional Regulation Questionnaire (CERQ-36), and the Short Dark Triad (SD-3). The results showed a good fit with the model in which Machiavellianism was indirectly and negatively related to CWB through the effect of maladaptive strategies and AWB, and indirectly and positively related to CWB through the effect of adaptive strategies and AWB. Narcissism was indirectly positively related to CWB through the effect of adaptive strategies and AWB. Finally, psychopathy was indirectly negatively associated with CWB through the effect of adaptive strategies and AWB. Limitations and clinical implications of this research are discussed.
Keywords: Narcisismo; Psicopatología; Personalidad - Trastornos; Dark triad; Machiavellianism; Psychopathy; Narcissism; Well-being; Emotion regulation strategies.